2019
DOI: 10.1177/2377960819848246
|View full text |Cite
|
Sign up to set email alerts
|

Rural Hospital Nursing Skill Mix and Work Environment Associated With Frequency of Adverse Events

Abstract: Introduction: Although rural hospitals serve about one fifth of the United States, few studies have investigated relationships among nursing resources and rural hospital adverse events. Objectives: The purpose was to determine relationships among nursing skill mix (proportion of registered nurses [RNs] to all nursing staff), the work environment, and adverse events (medication errors, patient falls with injury, pressure ulcers, and urinary tract infections) in rural hospitals. Methods: Using a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…54,55 Nurse staffing, on the other hand, has been linked to improved patient safety, lower mortality, shorter lengths of stay, lower readmissions, fewer complications, and increased profitability, 9,54-57 which may offset the higher costs with long-term savings from improved quality and health outcomes. 58 We found that the mortality index was strongly associated with a higher cost per patient day, which is consistent with the results from previous literature on hospital end-of-life care. 59,60 Although it was not the focus of our analysis, this may be attributable to socioeconomic factors and health disparities in rural areas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…54,55 Nurse staffing, on the other hand, has been linked to improved patient safety, lower mortality, shorter lengths of stay, lower readmissions, fewer complications, and increased profitability, 9,54-57 which may offset the higher costs with long-term savings from improved quality and health outcomes. 58 We found that the mortality index was strongly associated with a higher cost per patient day, which is consistent with the results from previous literature on hospital end-of-life care. 59,60 Although it was not the focus of our analysis, this may be attributable to socioeconomic factors and health disparities in rural areas.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has found that increased nursing staffing is associated with higher operating costs 54,55 . Nurse staffing, on the other hand, has been linked to improved patient safety, lower mortality, shorter lengths of stay, lower readmissions, fewer complications, and increased profitability, 9,54–57 which may offset the higher costs with long‐term savings from improved quality and health outcomes 58 . We found that the mortality index was strongly associated with a higher cost per patient day, which is consistent with the results from previous literature on hospital end‐of‐life care 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the dynamics of improved adverse event reporting relative to safe staffing cannot be oversimplified, as other elements such as leadership [ 75 ], teamwork [ 76 ], work environment [ 77 ], and communication [ 70 ] come into play. Adequate healthcare financing to address human and material resources against the background of complexities of growing global demand for health workforce amid COVID-19 can address the challenges associated with patient safety [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Looking at the impact of psychosocial work environment on recipient satisfaction, others find that the psychosocial work environment of nursing assistants and their satisfaction in their work can be increased by good leadership (Lundgren et al, 2019). A study among rural hospitals nurses on the association of work environment evidences that work environment is significantly associated with adverse events (Smith et al, 2019). Cooley, Pedersen, and Mainsbridge (2014) provide a better outcome in the workplace by implementing non-purposeful physical activity "e-health intervention" in a professional workplace.…”
Section: Literature Reviewmentioning
confidence: 99%